2018
DOI: 10.1097/cad.0000000000000596
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of belinostat with cisplatin and etoposide in advanced solid tumors, with a focus on neuroendocrine and small cell cancers of the lung

Abstract: The standard-of-care for advanced small cell lung cancer (SCLC) is chemotherapy with cisplatin+etoposide (C+E). Most patients have chemosensitive disease at the outset, but disease frequently relapses and limits survival. Efforts to improve therapeutic outcomes in SCLC and other neuroendocrine cancers have focused on epigenetic agents, including the histone deacetylase inhibitor belinostat. The primary objective was to determine the maximum tolerated dose of the combination of belinostat (B) with C+E. Belinost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…After analyzing these five pathways in CMap, several known compounds were identified. Unsurprisingly, many among the top 10 have been studied for the treatment of LUAD, including etoposide, irinotecan, resveratrol, and daunorubicin . This finding confirms that several well‐known anti‐cancer drugs used in LUAD treatment fulfill their function by targeting the five aforementioned signaling pathways.…”
Section: Discussionsupporting
confidence: 53%
“…After analyzing these five pathways in CMap, several known compounds were identified. Unsurprisingly, many among the top 10 have been studied for the treatment of LUAD, including etoposide, irinotecan, resveratrol, and daunorubicin . This finding confirms that several well‐known anti‐cancer drugs used in LUAD treatment fulfill their function by targeting the five aforementioned signaling pathways.…”
Section: Discussionsupporting
confidence: 53%
“…The study design and other details of this trial (NCT00926640) have been previously reported [46]. This trial was approved by the Institutional Review Board of the National Cancer Institute, and informed consent was obtained from all patients enrolled (Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…Platelet counts were obtained at several points throughout cycle 1, per protocol-mandated patient monitoring. All patients enrolled on this study were genotyped for UGT1A1 , as described previously [46]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though DNA DSBs had been detected by experimental methods such as the comet assay and pulsed-field gel electrophoresis previously, γ-H2AX is sensitive enough to detect radiation exposure equivalent to several mGy, and the operation is simple; therefore, it is widely used as a marker of DNA DSB [6,9,10]. Recently, the γ-H2AX assay is used as a method of monitoring in vivo DNA DSB level for clinical trials of novel anticancer drugs and for assessment of exposure dose of cancer patients who received radiation therapy [11][12][13][14][15][16][17]. Present when this manuscript is being written (June 2018), more than 40 clinical trials using the γ-H2AX assay seem to be performed in the United States (https://clinicaltrials.gov/).…”
Section: Introductionmentioning
confidence: 99%